2011
DOI: 10.1099/mic.0.051953-0
|View full text |Cite
|
Sign up to set email alerts
|

Genetic markers for Clostridium difficile lineages linked to hypervirulence

Abstract: Rapid identification of hypervirulent Clostridium difficile strains is essential for preventing their spread. Recent completion of several full-length C. difficile genomes provided an excellent opportunity to identify potentially unique genes that characterize hypervirulent strains. Based on sequence comparisons between C. difficile strains we describe two gene insertions into the genome of hypervirulent PCR ribotypes 078 and 027. Analysis of these regions, of 1.7 and 4.2 kb, respectively, revealed that they c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
42
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(44 citation statements)
references
References 46 publications
2
42
0
Order By: Relevance
“…It is currently among the top three most frequently encountered RTs in European hospitals (92,93,176). Furthermore, RT078 shares similar genetic features (binary toxin and tcdC mutations) and disease phenotypes (increased mortality and morbidity) with RT027 (28,109,176,177).…”
Section: Animal Reservoirs and Zoonotic Potentialmentioning
confidence: 99%
See 1 more Smart Citation
“…It is currently among the top three most frequently encountered RTs in European hospitals (92,93,176). Furthermore, RT078 shares similar genetic features (binary toxin and tcdC mutations) and disease phenotypes (increased mortality and morbidity) with RT027 (28,109,176,177).…”
Section: Animal Reservoirs and Zoonotic Potentialmentioning
confidence: 99%
“…This is interesting, as it shows that RT is indicative of not only differences in the amplified 16S-23S rRNA gene ISR but also specific differences in the nucleotide sequences of a number of conserved genes. Similarly, gene variations in hypervirulent RT027 and RT078 are MLST lineage specific (109).…”
Section: Phylogenetics and Molecular Epidemiologymentioning
confidence: 99%
“…Ribotype 176 is closely related to 027 [6,7] and can be misidentified by commercial tests targeting a singlebase-pair deletion at nucleotide 117 in the C. difficiletcdC gene [8]. In 2009, shortly afterward the 2008 study, the occurrence of ribotype 176 was reported in certain areas of the country (Eastern Bohemia and Moravia) [9].…”
Section: Introductionmentioning
confidence: 99%
“…lineages can be discriminated and several different PCR ribotypes have been shown to be closely related to the epidemic types using these sequence-based methods 98,230 . WGS is also used to study transmission and outbreaks 25,231 , although this approach can be costly and is predominantly performed retrospectively.…”
Section: Epidemiologymentioning
confidence: 99%